Hydrolytic Enzymes in KB Cells Infected with Poliovirus and Herpes Simplex Virus - Flanagan, John F. (1966)
Flanagan, John F. (Duke University School of Medicine, Durham. N.C.). Hydrolytic enzymes in KB cells infected with poliovirus and herpes simplex virus. J. Bacteriol. 91:789–797. 1966.—The effect of poliovirus and herpes simplex virus infection on the activity of five hydrolytic enzymes was studied in tissue culture cells of KB type. During the course of poliovirus infection, the activity of β-glucuronidase, acid protease, acid ribonuclease, acid deoxyribonuclease, and acid phosphatase in the cytoplasm rose to levels two- to fourfold greater than the activity present in the cytoplasm of uninfected cells. The rise in cytoplasmic activity was accompanied by a concomitant decrease in enzymatic activity bound to cell particles. Shift of enzymatic activity from the particulate to soluble state was first detected at 6 hr after poliovirus infection, coinciding with the appearance of new infectious particles and virus cytopathic effect. No net synthesis of these enzymes after poliovirus infection was found. Hydrocortisone added to the culture medium failed to affect either the titer of virus produced in the cells or the release of hydrolytic enzymes from the particulate state. Herpes simplex infection produced minimal alterations in the state of these enzymes in KB cells. It is hypothesized that the breakdown of lysosomes and release of hydrolytic enzymes accompanying poliovirus infection is produced by alterations in cell membrane permeability during the course of virus replication and by the consequent change in the ionic content of the cell sap.